2011
DOI: 10.1242/jcs.083634
|View full text |Cite
|
Sign up to set email alerts
|

Protein 4.1R regulates cell migration and IQGAP1 recruitment to the leading edge

Abstract: In red blood cells, multifunctional protein 4.1R stabilizes the spectrin–actin network and anchors it to the plasma membrane. To contribute to the characterization of functional roles of 4.1R in nonerythroid cells, we have analyzed the participation of protein 4.1R in cell migration. The distribution of endogenous 4.1R is polarized towards the leading edge of migrating cells. Exogenous 4.1R isoforms containing a complete membrane-binding domain consistently localized to plasma membrane extensions enriched in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 42 publications
2
39
0
Order By: Relevance
“…3B). As described before, ECV304 cells contain several 4.1R isoforms (Ruiz-Sáenz et al, 2011), which are mainly produced by alternative splicing (Conboy, 1999;Tang et al, 1990). Although several 4.1R isoforms were found in the cell extract, only the ,80-kDa 4.1R species was detected in the GFP-CLASP2 immunoprecipitates (Fig.…”
Section: Protein 41r Interacts With Clasp2supporting
confidence: 62%
See 4 more Smart Citations
“…3B). As described before, ECV304 cells contain several 4.1R isoforms (Ruiz-Sáenz et al, 2011), which are mainly produced by alternative splicing (Conboy, 1999;Tang et al, 1990). Although several 4.1R isoforms were found in the cell extract, only the ,80-kDa 4.1R species was detected in the GFP-CLASP2 immunoprecipitates (Fig.…”
Section: Protein 41r Interacts With Clasp2supporting
confidence: 62%
“…In addition, a role for 4.1R as a linker between the actin cytoskeleton and components of tight junctions (Mattagajasingh et al, 2000) and adherens junctions (Yang et al, 2009) has been reported. Recently, we showed that 4.1R selectively accumulates at the leading edge of migrating cells and that its depletion affects cell motility (Ruiz-Sáenz et al, 2011). All these findings indicate that 4.1R is not only an adaptor protein linking transmembrane proteins and the actin cytoskeleton but also a multifunctional protein acting at different subcellular sites.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations